Re-thinking Chinese Ecumene in the Global Age - Duraj, Jaroslaw (Eric Voegelin’s Asian Political Thought, 2020)
The rise of Asia in global affairs has forced western thinkers to rethink their assumptions, theories, and conclusions about the region. Eric Voegelin’s Asian Political Thought brings together a mixture of established and rising scholars from both Asia and the West to reflect upon the political philosopher’s thought about China, Japan, Korea, Central Asia, and India. From Voegelin’s writings, readers will not only understand how Voegelin’s approach can illuminate the fundamental principles and issues about Asia but also what are the challenges and possibilities that Asia offers in the twentieth-first century. For those who want to move past the superficial commentary and clichés about Asia, Eric Voegelin’s Asian Political Thought is the book for you.

La Dottrina Sociale della Chiesa in Cina. Un riferimento per l’etica degli affari (“Catholic Social Teaching in China. A reference for Business Ethics”) - Rothlin, Stephan (La Chiesa in Cina. Un future da scrivere, 2019)

Catholic social teaching and environmental responsibility - Rothlin, Stephan; McCann, Dennis (A planetary and global ethics for climate change and sustainable energy, 2016)

International Business Ethics. What We Have Learnt by Focusing on China? - Rothlin, Stephan; McCann, Dennis (Eine Wirtschaft, die Leben fördert. Wirtschafts- und unternehmensethische Reflexionen im Anschluss an Papst Franziskus, 2017)